Glycogen Metabolism and Brain Pathologies - Cloix, Jean-Francois; Ardourel, Marie-Yvonne; Hevor, Tobias (Central Nervous System Agents in Medicinal Chemistry, 2008)
Glucose is the main fuel for cell life, and supports a number of different processes in providing cells with energy. Excess glucose is polymerized into glycogen, which is an energy-glucose store. Alterations in glycogen content and/or synthesis have been reported in human neuropathologies, such as Alzheimer's disease, epilepsies and cancer. Epileptic foci are hypometabolic during the interictal period, and probably hypermetabolic during crisis. Animal models of epilepsies are used for studying the reasons why neurons suddenly and temporally synchronize their activity. One model associates seizures of the “grand mal” type with cortical glycogen accumulation: induction of epileptiform crisis by methionine sulfoximine (MSO). The glycogen accumulation, observed in astrocytes only, occurs as soon as the preconvulsive period. High glycogen has also been demonstrated in primary cultures of astrocytes. Abnormal glycogen content has been characterized in various types of cancers, including gliomas. High invasion properties, spontaneous resistance to chemotherapeutic drugs, and a mean prognosis of 12 months characterize glioblastomas, the highest grade of gliomas that inevitably leads to death. The various therapeutic means, including surgery, chemicaland radio-therapies, and gene therapy have thus far been inefficient in significantly improving patient survival. Glycogen synthesis was targeted in cell lines from murine and human glioblastomas by an antisense glycogen synthase cDNA strategy; and the inhibition of glycogen synthesis in these cell lines decreases both in vitro and in vivo invasiveness. Glycogen can therefore be considered as putatively involved in at least two different pathologies of the brain, such as epilepsies and cancer. This abnormal glycogen content and synthesis can be proposed as putative diagnostic and therapeutic targets in brain pathologies.
Keywords: Neuropathology